The Evolution of Spite, Recognition, and Morality. - Forber, Patrick.; Smead, Rory. (Tufts University. Tisch Library., 2017)
Recognition of and responsiveness to the behavioral dispositions of others are key features of moral systems for facilitating social cooperation and the mediation of punishment. Here we investigate the coevolutionary possibilities of recognition and conditional social behavior with respect to both altruism and spite. Using two evolutionary models, we find that recognition abilities can support both spite and altruism but that some can only coevolve with spite. These results show that it is essential to consider harmful social behaviors as both a product of and an influence on the core features of our moral systems.